Commercialization of pearl millet: Seed production and value addition - Jacob, Jinu; Reddy, P Sanjana (Indian Farming, 2023)
Pearl millet (Pennisetum glaucum), is the sixth most important global cereal and the millet occupying largest area in India. As a versatile crop that provides food, feed and fodder, and survives in the arid and semi-arid tropics with minimum inputs, pearl millet is regarded as a promise for future farming. Good quality seed is a vital input for exploiting complete potential of crop production. This article elaborately describes the seed production programmes in pearl millet. The significance of value addition in the crop for food and other uses is also described.